Catheter‐related bloodstream infection in patients With severe anorexia nervosa. Issue 4 (13th February 2022) - Hirata, Takashi; Yasuda, Kazuyuki; Iwata, Yusuke; Uemura, Takuji; Aruga, Yu; Shioe, Risa; Uchinuma, Niina; Tamaoki, Toshio; Suzuki, Takefumi
Abstract: Purpose: Anorexia nervosa (AN) may be treated with intravenous hyperalimentation (IVH) that may be associated with catheter‐related bloodstream infection (CRBSI). Design and Methods: Retrospective chart review was conducted to compare those who developed CRBSI were compared with those who did not. Findings: Of 34 patients, 17 episodes of AN treated with IVH were identified, of which five resulted in CRBSI. The average body mass index at admission was low at 12.2. Patients who needed physical restraint during IVH had a higher (albeit statistically nonsignificant) risk. Also, those with purging had numerically lower risk. Practice Implications: CRBSI complicated IVH in 29.4% instances of severe life‐threatening AN in our sample. Whether physical restraints and no purging constitute a risk factor of CRBSI needs to be further investigated.